1994
DOI: 10.1007/bf00306113
|View full text |Cite
|
Sign up to set email alerts
|

A newly discovered pathway of melanin formation in cultured retinal pigment epithelium of cattle

Abstract: According to a recent hypothesis the melanin granules in the retinal pigment epithelium of mammals originate from photosensory membrane degradation. To test this hypothesis the retinal pigment epithelium of cattle was kept in tissue culture and exposed to gold-labelled rod outer segments. Gold granules were later detected inside phagosomes, melanosomes and mature melanin granules. Tyrosinase, the key enzyme in melanogenesis, was additionally localized inside phagosomes. These results indicate that in cultured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
0

Year Published

1999
1999
2007
2007

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 46 publications
(55 citation statements)
references
References 20 publications
9
44
0
Order By: Relevance
“…Tyrosinase has been found in the adult RPE of cattle [5] and in cultivated RPE cells [6]. Furthermore, it was demonstrated that melanogenesis takes place in cultivated RPE cells of cattle, following feeding with rod outer segments (ROS) [6]. These findings are consistent with the study of Zhu et al [7], who found that adult RPE cells can produce new melanin.…”
Section: Introductionsupporting
confidence: 82%
See 3 more Smart Citations
“…Tyrosinase has been found in the adult RPE of cattle [5] and in cultivated RPE cells [6]. Furthermore, it was demonstrated that melanogenesis takes place in cultivated RPE cells of cattle, following feeding with rod outer segments (ROS) [6]. These findings are consistent with the study of Zhu et al [7], who found that adult RPE cells can produce new melanin.…”
Section: Introductionsupporting
confidence: 82%
“…In the RPE cells we found very few undigested ROS in phagolysosomes ( fig. 2), showing that the ROS of the cattle were decomposed by the RPE cells of the rats as found in vitro [6]. As shown in figure 3 and table 1, we found an increase in the number of early-stage melanosomes and small melanin granules in the eyes with ROS injection compared to eyes without injection.…”
Section: Resultssupporting
confidence: 59%
See 2 more Smart Citations
“…These data therefore suggest that RABRP1 functions in the vesicle transport pathway toward lysosomes and/or its related structures. Recently, in mammalian pigment cells (melanocytes), it has been suggested that melanosomes, organelles containing the melanin pigment, are specialized forms of late endosomes or lysosomes, and are formed through a similar pathway to that of lysosomes (Jimbow et al, 1997;Schraermeyer and Stieve, 1994;Vijayasaradhi et al, 1995). Furthermore, in Drosophila, several kinds of proteins required for vesicle traffic to lysosomes are also essential for biogenesis of pigment granules: garnet gene product, which functions in the delivery of proteins to pigment granules, was identified as the δ-subunit of the AP-3 adaptor complex that was involved in the Golgi-to-lysosome pathway (Cowles et al, 1997;Le Borgne et al, 1998;Ooi et al, 1997;Simpson et al, 1997).…”
Section: A Possible Function Of Rabrp1mentioning
confidence: 99%